LOCAL AWARENESS IN THE TRADITION OF BALIMAU PAGA TO WELCOME THE HOLY MONTH OF RAMADHAN IN KAMBANG IN PESISIR SELATAN DISTRICT - Nanda Safira (SEMESTA: Journal of Science Education and Teaching, 2021)
This study was conducted to determine the implementation process of the Balimau Paga tradition, the meaning contained in the Balimau Paga tradition and the shifts that occur in the implementation of the Balimau Paga tradition in Kambang sub-district, Pesisir Selatan Regency. This type of research is qualitative using descriptive methods. The research data were collected by conducting observations, interviews and documentation studies. The results showed that the process of implementing Balimau Paga was carried out a day before entering the holy month of Ramadan. This tradition is carried out by the community, where, Balimau with lime brought by nephews. From the results of this study it can be concluded that the Balimau Paga tradition is starting to experience irregularities. Therefore it is recommended to all community members to maintain the Balimau Paga custom or tradition that has been preserved and carried out by previous generations by consistently implementing it.